2010
DOI: 10.1016/j.crvi.2010.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of polyphenolic compounds, in vitro antioxidant and anti-inflammation properties of Securidaca longepedunculata root barks

Abstract: The present study was carried out to evaluate the antioxidant activities of the root bark extract of Securidaca longepedunculata. This plant material is commonly used in folk medicine in several parts in the world. The bark extracts of S. longepedunculata were evaluated for their total phenols, flavonoids, anthocyanins, tannins content and total antioxidant capacity. The compounds were identified and quantified both by RP-HPLC and UV spectrophotometer; the antioxidant capacity was assessed by ABTS and DPPH tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 28 publications
2
27
0
1
Order By: Relevance
“…The aqueous methanol extract (50%) of the root bark exhibited an IC 50 of 1.351 and 9.48 µg/ml against ABTS and DPPH respectively (Muanda et al, 2010). Although the extraction methods of the leaf and root bark were slightly different, these results may well suggest that the root bark extract quenches DPPH much better than the leaf extract.…”
Section: Antioxidant Activitymentioning
confidence: 61%
See 2 more Smart Citations
“…The aqueous methanol extract (50%) of the root bark exhibited an IC 50 of 1.351 and 9.48 µg/ml against ABTS and DPPH respectively (Muanda et al, 2010). Although the extraction methods of the leaf and root bark were slightly different, these results may well suggest that the root bark extract quenches DPPH much better than the leaf extract.…”
Section: Antioxidant Activitymentioning
confidence: 61%
“…The water and aqueous methanol extracts from the root yielded a variety of compounds in varying amounts, including gallic acid, chlorogenic acid, caffeic acid, epicatechic acid, rutin, p-coumaric acid, cinnamic acid, apigenin, quercetin glucosyl and quercetin dihydrate (Muanda et al, 2010). Four highly oxygenated xanthones, muchimangins A-D, with a diphenylmethyl substituent have also been isolated from the root as minor constituents (Dibwe et al, 2012).…”
Section: Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, low-fat diet [22], fruit [25], tomatoes [23,26], nuts [27], whole grains [21,28], fish [29], and, especially, nutrients from foods rich in phytochemicals or antioxidants (e.g. carotene, lycopene, vitamin C, flavonoids [30][31][32]) have been found to have anti-inflammatory properties. In contrast, high-fat foods (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pharmacological studies on S longepedunculata showed some anti-inflammatory, antiulcer, antianemia and antiplasmodial properties of this species extracts (Ojewole et al, 2008). Furthermore, phytochemical investigations of several parts of the plant revealed presence of saponins (Ndamitso et al, 2013;Stevenson et al, 2009), flavonoids (Auwal et al, 2012;Muanda et al, 2010), alkaloids (Wrobel et al, 1996), steroids (Meli et al, 2007), sucrose derivatives (De Tommasi et al, 1993), phenolic acids (Muanda et al, 2010) and volatile oils (Nebié et al, 2004;Jayasekara et al, 2005). Although a lot of medicinal plants are widely used and assumed to be safe, they could potentially be toxic (Nasri and Shirzad, 2013).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%